The ecology of black guillemots Cepphus grylle in Shetland - Ewins, P; Ewins, Pete (2016)
Following a large kill of Black Guillemots in the Esso Bernicia oil spill in Shetland, this study was initiated to determine the population size and distribution of the species at different times of year and to investigate its ecology. The results will enable oil spill contingency plans to be made for this species and provide a base-line against which future work can be compared. This is the first major study of Black Guillemots in the UK. There were large diurnal and seasonal fluctuations in colony attendance patterns which were investigated in relation to various factors. Reliable census techniques were devised and suitable stretches of coastline were established as monitoring units. Black Guillemots rarely foraged in water more than 40-50 m deep, and seldom moved more than 3 km from the nest during the breeding season. The proximity of suitable breeding sites to shallow water feeding grounds accounted for the fairly regular breeding dispersion. On islands with mammalian predators only nest sites in inaccessible cliffs were used. In many areas breeding numbers were limited by nest site availability. The distribution at other times of year was more irregular. After breeding adults congregated in traditional moulting areas where they became flightless for 4-5 weeks. These flocks of up to c.600 adults constitute vulnerable "hot spots" at which the effect of oil pollution would be most severe. In winter there was some movement away from exposed coasts, resulting in concentrations in more sheltered, inshore waters. A wide range of fish and invertebrates were eaten by adults, largely reflecting the diversity of inshore benthic communities. There appears to be a greater dependence on invertebrates during the winter months, when fish are scarcer. Chicks were fed almost exclusively on fish: their diet composition was determined primarily by local availability, although some adults specialised on particular species. When large gadoid fish became available in late summer adults were able to provide more energy per feed ...